2012
DOI: 10.1093/geront/gns044
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality Traits Moderate the Impact of Care Receipt on End-of-Life Care Planning?

Abstract: Health practitioners should take into account older adults' care needs and differing personality traits while helping older adults make successful EOLCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Individuals high on openness and agreeableness have been seen to utilize complementary and alternative medicine services more readily [12] and a large population-based study found that higher levels of both conscientiousness and agreeableness were associated with a greater likelihood of end-of-life care planning [13]. However, past research indicates that elevated levels of neuroticism may be particularly salient for health care providers to evaluate and consider when tailoring treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals high on openness and agreeableness have been seen to utilize complementary and alternative medicine services more readily [12] and a large population-based study found that higher levels of both conscientiousness and agreeableness were associated with a greater likelihood of end-of-life care planning [13]. However, past research indicates that elevated levels of neuroticism may be particularly salient for health care providers to evaluate and consider when tailoring treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This factor can be an important coping resource for stressed situations, making some individuals better prepared than others to deal with these conditions. Dedication and proactive planning are some characteristics of this factor that can support patients to follow medical commands and strict treatments easily …”
Section: Discussionmentioning
confidence: 99%
“…People with high agreeableness are qualified as more acceptable and tolerable and can be less likely to do things in their own way, cooperating more with their caregivers and following the health team recommendations . Another feature of this personality factor, “willingness to please others,” can lead people to speak openly about their doubts regarding treatment and request the opinion of family members and health professionals, causing a positive effect when these patients receive satisfactory and proper care …”
Section: Discussionmentioning
confidence: 99%
“…Those who regularly interact with health care providers are more likely to complete advance directives ( Rao et al, 2014 ). Experiencing day-to-day discriminatory treatment has also been found to decrease agreeableness and conscientiousness in older adults ( Sutin, Stephan, & Terracciano, 2016 ), personality traits which have been linked to willingness to engage in ACP ( Carr, 2012 ; Ha & Pai, 2012 ). Major discriminatory events may impact health behaviors, including ACP, by undermining trust in health and other institutions as well as contributing to the accumulation of disadvantages in informational, financial, and social resources that leads to health disparities ( Phelan, Link, & Tehranifar, 2010 ).…”
Section: Background and Objectivesmentioning
confidence: 99%